2022
DOI: 10.3390/ijerph192013243
|View full text |Cite
|
Sign up to set email alerts
|

How Social Determinants of Health of Individuals Living or Working in U.S. Department of Veterans Affairs Home-Based Long-Term Care Programs in Puerto Rico Influenced Recovery after Hurricane Maria

Abstract: In September 2017, Hurricane Maria devastated Puerto Rico, causing extensive infrastructure damage and a significant number of deaths. In the months and years since, recovery from Maria has been slow, hampered by delayed delivery of fiscal aid, corruption, economic hardships, and Puerto Rico’s colonial status. Simultaneously, Puerto Rico’s population is rapidly aging and hundreds of thousands of mostly younger Puerto Ricans are migrating out of Puerto Rico for more opportunities. Many Puerto Ricans who are old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The proactive nature of the VA HBPC staff to create a new workgroup to improve future disaster preparedness and response and tracking systems to call Veterans before and after a disaster are examples that other institutions and groups that care for older adults who are primarily homebound can model. This is critical, as past research has shown time and again how older adults with complicated health histories are particularly vulnerable to hurricanes [ 27 , 28 ]. One study conducted in Puerto Rico following Hurricane Maria interviewed Veterans, their caregivers, and VA staff in home-based long-term care settings, regarding how social determinants of health influenced recovery from the hurricane [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proactive nature of the VA HBPC staff to create a new workgroup to improve future disaster preparedness and response and tracking systems to call Veterans before and after a disaster are examples that other institutions and groups that care for older adults who are primarily homebound can model. This is critical, as past research has shown time and again how older adults with complicated health histories are particularly vulnerable to hurricanes [ 27 , 28 ]. One study conducted in Puerto Rico following Hurricane Maria interviewed Veterans, their caregivers, and VA staff in home-based long-term care settings, regarding how social determinants of health influenced recovery from the hurricane [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is critical, as past research has shown time and again how older adults with complicated health histories are particularly vulnerable to hurricanes [ 27 , 28 ]. One study conducted in Puerto Rico following Hurricane Maria interviewed Veterans, their caregivers, and VA staff in home-based long-term care settings, regarding how social determinants of health influenced recovery from the hurricane [ 28 ]. Applying the social ecological model of health, many interconnected social determinants played a role, including the strength of social networks, VA and local policies and support, the receipt of needed aide, and governmental and non-governmental partnerships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed how people with a strong community recovered better from health problems acquired by the hurricane. They emphasized that the effect of a united community not only had an impact on the direct help that person could receive, but also on his or her predisposition and will to recover and adhere to treatment [36]. As can be seen, the SDoH impact on the recovery of individuals and, in turn, during the recovery cycle, they also undergo modifications.…”
Section: Sdoh Dynamism and Impact On Patientsmentioning
confidence: 99%